Learning Atmosphere During The Covid-19 Pandemic - Edi Wiranto; Muhammad Kristiawan; Yessy Fitriani (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
This study aims to determine the atmosphere of the academic in the midst of covid-19 pandemic at SD Negeri 169 Ogan Komering Ulu (OKU). The formulation of the problem in this study: (1) what is the academic atmosphere of SD Negeri 169 OKU in the midst of the Covid-19 pandemic?, (2) what are the inhibiting factors in creating an academic atmosphere at SD Negeri 169 OKU in the midst of the Covid-19 pandemic?. The type of research used is qualitative research with using qualitative descriptive analysis data. The data collection technique is done by interview, observation, documentation and triangulation. The results of the study were seen from the academic atmosphere and inhibiting factors in creating an academic atmosphere in the midst of the Covid-19 pandemic. In the academic atmosphere, the teaching and learning process at SD Negeri 169 OKU was running safely, orderly and conducive. The learning activity is distance and offline learning while adhering to health protocols in accordance with directions and instructions from the OKU District Education Office. Meanwhile, the inhibiting factors in creating an academic atmosphere in the midst of the Covid-19 pandemic are (1) teachers find it difficult to evaluate student learning outcomes, (2) internet network constraints, (3) power lines that often go out, (4) not all students have smartphones and internet pulses, and (5) some students did not collect or send assignments given by the teacher.